Cognitive Defusion Is a Core Cognitive Mechanism for the Sensory-Affective Uncoupling of Pain During Mindfulness Meditation. Issue 6 (July 2021) - Zorn, Jelle; Abdoun, Oussama; Sonié, Sandrine; Lutz, Antoine
ABSTRACT: Objective: Mindfulness meditation can downregulate the experience of pain. However, its specific underlying regulatory mechanisms are still largely unknown. Here, we aimed to investigate the role of cognitive defusion—a form of psychological distancing from internal experiences—in mindfulness-based pain regulation. Methods: We implemented a thermal heat paradigm that was designed to amplify the cognitive-affective aspects of pain in 43 novice meditators (2-day formal training; 51.2% women; 53.2 ± 7.0 years old) and 27 expert meditators (>10, 000-hour practice; 44.4% women; 51.9 ± 8.4 years old). We collected pain intensity and unpleasantness reports and trait measures of pain catastrophizing assessed by the Pain Catastrophizing Scale (PCS), cognitive defusion assessed by the Drexel Defusion Scale (DDS), and cognitive fusion assessed by the Cognitive Fusion Questionnaire, as well as of several other constructs commonly reported in the literature. Results: Experts reported lower PCS (6.9 ± 5.2 versus 17.2 ± 8.5, p < .001) but higher DDS (39.4 ± 6.4 versus 28.9 ± 6.6, p < .001) than novices. Across participants, the PCS and DDS were negatively correlated and shared unique variance that survived adjusting for other mindfulness-related and cognitive-emotional constructs (β = −0.64, p < .001). Conversely, the relationships between PCS and other commonly reported constructs did not seem specific, as none of the relationships survived adjusting for DDS (adjusted β < 0.25, p > .05). Further supporting the relevance of DDS to pain, both the DDS and PCS specifically predicted pain unpleasantness as opposed to pain intensity. However, DDS seemed to be a more specific predictor of unpleasantness than PCS, as the relationship between DDS and unpleasantness survived adjusting for PCS (adjusted β = −0.33, p = .016), but not vice versa (adjusted β = 0.20, p = .162). We also found that the Cognitive Fusion Questionnaire showed a similar pattern of associations with PCS and pain self-reports to what was found for the DDS, although these associations were less consistent. Conclusions: Collectively, these findings highlight the central role of cognitive defusion in mindfulness-based pain regulation. Abstract : Supplemental digital content is available in the text.